Socio-cultural of developmental milestones in infancy in South West Nigeria: a qualitative study (2015)
Developmental milestones are generally understood to be milestones of neurological development such as neck control, sitting without support, crawling and standing. Child health care providers routinely use normative data on such milestones to evaluate child development. However, there is often a cultural context to expectations of developmental milestones. The goal of this research is to explore the socio-cultural context of developmental milestones in infancy in a Nigerian community. In-depth interview was conducted with 30 mothers enrolled from an infant welfare clinic, southwest, Nigeria The transcripts were coded and analyzed using the Atlas ti 7.0 software package in a combination of thematic and narrative approaches. Mean age of participants was 33.3 (SD 5.1) years, 73% were married, 80% had two or more older children. Mothers expect that a child will be able to sit unaided, crawl and be able to stand by the age of one year. Opinion was divided about if it was possible to predict the age a child will attain a specific milestone. Most mothers reported that the age at which babies attain developmental milestones depends on childrearing practices utilized by the mother. Other factors they perceive as influencing developmental milestones include: having siblings, the age at which siblings and/or parents achieve similar milestones and the environment the child is reared in. Teething was considered an important milestone which has specific culture-bound connotations. Walking was considered one of the most significant milestones, not only indicating normal development but also signifying some independence for both mother and child. In this study of Nigerian mothers, developmental milestones in the first year of life have recognized influencing factors and a number of specific culture-bound associated beliefs. This exploratory study provides insights into intersections between biomedical and cultural concepts of childhood development.